2017
DOI: 10.1037/sgd0000211
|View full text |Cite
|
Sign up to set email alerts
|

Trends in suicidality among sexual minority and heterosexual students in a canadian population-based cohort study.

Abstract: Objectives-Despite evidence from numerous studies that document disparities in suicidality for sexual minorities, few have investigated whether or not these trends have improved over time, which is the objective of the current study.Methods-Using school-based population data over a 15-year period (1998 to 2013), multivariate logistic regressions were used to calculate age-adjusted odds ratios separately by gender. Interactions were included to test widening or narrowing disparities within orientation groups, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
(48 reference statements)
6
32
0
2
Order By: Relevance
“…While same‐gender love had a similar prevalence across genders, more than twice as many girls reported love for both‐gender partners than boys. This is comparable with observations from other population‐based studies of adolescents (e.g., Goodenow, Watson, Adjei, Homma, & Saewyc, 2016; Peter et al., 2017) and longitudinal studies which suggest that women's attraction is more “fluid” and maybe more determined by situational factors than that of men (Umberson, Thomeer, Kroeger, Lodge, & Xu, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…While same‐gender love had a similar prevalence across genders, more than twice as many girls reported love for both‐gender partners than boys. This is comparable with observations from other population‐based studies of adolescents (e.g., Goodenow, Watson, Adjei, Homma, & Saewyc, 2016; Peter et al., 2017) and longitudinal studies which suggest that women's attraction is more “fluid” and maybe more determined by situational factors than that of men (Umberson, Thomeer, Kroeger, Lodge, & Xu, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five 1,7,12,18,[20][21][22][35][36][37][38][39][40][41][42][43][44][45][46][47][48] studies reported in 24 articles that involved a total of 2 378 987 heterosexual and 113 468 sexual minority adolescents (age range, 12-20 years) were included in the analysis (Figure 1). The studies were conducted in 10 countries (Iceland, United States, Ireland, Canada, Switzerland, Norway, New Zealand, China, Taiwan, and Korea).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sensitivity analysis, in which the meta-analysis was serially repeated after the exclusion of each study, showed that most studies affected the overall OR at an SD of 0.07 except for 3 studies: exclusion of the study by Lucassen et al 18 from the total sample revealed a decrease in OR to 3.31 (95% CI, 2.82-3.90), exclusion of National American Indian Adolescent Health Survey of 1990 from the study by Saewyc et al 42 revealed an increase in OR to 4.05 (95% CI, 3.58-4.59), and exclusion of the Minnesota Student Survey of 1992 in the study by Saewyc et al 42 revealed an increase in OR to 3.61 (95% CI, 3.10-4.22). Exclusion of the study by Peter et al 22…”
Section: Prevalence Of Attempted Suicide Among Sexual Minority Adolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wohlbefinden aufweisen als cisgeschlechtliche oder Personen, die nicht trans sind. Die Ergebnisse zeigen, dass junge Menschen aus sexuellen Minoritäten, und damit auch Transgender-Kinder und -Jugendliche, trotz wachsender gesellschaftlicher Akzeptanz von Geschlechtsinkongruenz, Gendervarianz und Transgender einer besonderen Belastung und Risiken hinsichtlich ihrer psychischen Gesundheit ausgesetzt sind -und somit auch entsprechender Hilfsangebote bedürfen‚[44]. Beziehungen nicht "abpuffern", es gab also keine Interaktionseffekte zwischen den Risikofaktoren für die psychische Entwicklung.…”
unclassified